Women in a region with high incidence of cervical cancer warrant immediate colposcopy for low-grade squamous intraepithelial lesion on cervical cytology - Phongnarisorn C. (2014)
The objective of this study was to determine the prevalence of high-grade histologic diagnoses in women who had low-grade squamous intraepithelial lesion (LSIL) on Pap smear in an area with high incidence of cervical cancer. We conducted a retrospective study of 220 women with LSIL cytology undergoing colposcopic examination in Chiang Mai University Hospital between January 1999 and July 2004. The histologic diagnoses, obtained from colposcopically directed biopsy or electrical loop excision after initial colposcopy, showed that 80 (36.4%) women had histologically confirmed high-grade lesions and 11 (5%) women had microinvasive (9) and frankly invasive (2) carcinomas. Overall, 41.5% of women with LSIL on Pap smear had significant underlying lesions, requiring appropriate treatment. In conclusion, in the region with high incidence of cervical cancer, women with LSIL cytology are at increased risk of having underlying high-grade lesions and invasive cancer. Immediate referral for colposcopy is warranted.